Role of nickel doping on structural, optical, magnetic properties and antibacterial activity of ZnO nanoparticles. (April 2016) - Vijayaprasath, G.; Murugan, R.; Palanisamy, S.; Prabhu, N.M.; Mahalingam, T.; Hayakawa, Y.; Ravi, G.
Graphical abstract: Highlights: The XRD analyses revealed that the synthesizes nickel doped ZnO (Zn1− x Ni x O, x = 0.0, 0.03, 0.06 and 0.09) nanostructures have hexagonal wurtzite structure. The photoluminescence measurements revealed that the broad emission was composed of different bands due to zinc and oxygen vacancies. X-ray photoelectron spectroscopy (XPS) confirmed the Ni incorporation in ZnO lattice as Ni 2+ ions. Room temperature ferromagnetism was observed due to the oxygen vacancies and zinc interstitials are the main reasons for ferromagnetism in Ni doped ZnO NPs. Abstract: Zn1− x Ni x O nanoparticles were synthesized by co-precipitation method. The crystallite sizes of the synthesized samples found to decrease from 38 to 26 nm with increase in nickel concentration. FTIR spectra confirmed the presence of ZnO stretching bands at 577, 573, 569 and 565 cm −1 in the respective ZnO NPs. Optical absorption spectra revealed the red shifted and estimated band gap is found to decrease with increase of Ni doping concentration. The PL spectra of all the samples exhibited a broad emission at 390 nm in the visible range. The carriers (donors) bounded on the Ni sites were observed from the micro Raman spectroscopic studies. Pure and Ni doped ZnO NPs showed significant changes in the M–H loop, especially the diamagnetic behavior changed into ferromagnetic nature for Ni doped samples. The antiferromagnetic super-exchange interactions between Ni 2+ ions is increased in higher Ni doped ZnO NPs and also their antibacterial activity has been studied.